Effectiveness of arbuscular mycorrhiza and calcite on soil macronutrient content and P uptake in palmarosa (Cymbopogon martinii) - Samanhudi; Setyawati Andriyana; Rahayu Muji; Purnomo Djoko; Syahrina Aulia Fidia (BIO Web of Conferences)
Macronutrient levels are critical to support the sustainability and consistency of crop production of palmarosa. This study aims to determine the soil macronutrient content and the phosphorus uptake of palmarosa that cultivated with arbuscular mycorrhiza fungi (AMF) and calcite at various dosages. Experiment through a completely randomized design using AMF and calcite, each with four levels: AMF (0, 5, 15, and 25 g plant-1) and calcite (0, 2.5, 5, 7.5 tons ha-1). The results showed that the soil condition before AMF and calcite treatment was marginally suitable for palmarosa due to low available P content (7 ppm). The application of calcite increased soil calcium content by 114% directly proportional to the level of soil pH (7.3-7.6) which was positively correlated with the increase in calcite dosages. Dosages of AMF 25 g plant-1 and calcite 2.5 tons ha-1 suggested to be applied in Tawangmangu, Central Java, to improve soil suitability for palmarosa growing conditions. This application efficiently increases soil macronutrient content, particularly in enhancing the levels of soil P2O5 by 281%, available P by 57%, and P uptake in palmarosa by 82%.